Qualitative analysis of mental health service users' reported experiences of discrimination. (August 2016) - Hamilton, S.; Pinfold, V.; Cotney, J.; Couperthwaite, L.; Matthews, J.; Barret, K.; Warren, S.; Corker, E.; Rose, D.; Thornicroft, G.; Henderson, C.
Abstract : Objective: To better understand mental health service users' experiences of stigma and discrimination in different settings. Method: An annual telephone survey of people with a mental health diagnosis conducted to evaluate the Time to Change antistigma campaign in England. Of 985 people who participated in 2013, 84 took part in a qualitative interview which was audio recorded. Of these, 50 interviews were transcribed and thematically analysed to explore accounts of discrimination. We analysed common types of behaviour; motivations ascribed to the discriminators; expectations of what fair treatment would have been; and the impact of discrimination on participants. Results: Discrimination was most common in five contexts: welfare benefits, mental health care, physical health care, family and friends. Participants often found it hard to assess whether a behaviour was discriminatory or not. Lack of support, whether by public services or by friends and family, was often experienced as discrimination, reflecting an expectation that positive behaviours and reasonable adjustments should be offered in response to mental health needs. Conclusion: The impact of discrimination across different settings was often perceived by participants as aggravating their mental health, and there is thus a need to treat discrimination as a health issue, not just a social justice issue.